Embracing Blended Learning as the Pathway to the Future Education: Students’, Teachers’, and Experts’ Perspectives - Sameer Mosa Mohammed AlNajdi (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
This study aimed to determine the efficacy of blended learning in the future of education by uncovering the students’ and teachers’ Perspectives on blended learning. Qualitative research was applied by interviewing 23 students and 27 teachers from elementary to high school through Microsoft Teams. Data was then managed, organized, encoded, and classified using NVivo to interpret the results. Students and teachers attended a group meeting to encourage them to examine their perceptions of adopting blended learning, and motivating techniques were utilized at the beginning of the interview to clarify the study’s goal. Then, an individual interview for each participant with open-ended questions to record their perspective. Results showed that students reported that blended learning allows them to review and discuss the lesson with their teachers, especially those who used flipped classrooms. Also, teachers stated they had difficulty motivating their students in online classes. However, blended learning prevented our students from losing during the classes because they could attend the classroom and discuss all their concerns with them. Blended learning is becoming increasingly popular in education. There are several reasons why it will be the future of education, such as its flexibility, personalization, engagement, cost-effective, and advances in technology, which allow students to learn at their own pace and on their schedule, receive personalized instruction tailored to their needs and learning styles, combines the best of both worlds-traditional classroom learning and online learning, more cost-effective than traditional classroom teaching, and become even more effective and efficient with the technological inventions. Experts reported that following instructional design procedures will create an effective blended learning experience.